In Vitro Study of Tooth Surfaces After Interproximal Enamel Reduction: Extraoral Scanner and SEM Analysis - Francesca Cremonini; Viviana Giannoccaro; Mario Palone; Paolo Albertini (Association of Support to Oral Health Research (APESB), 2021)
Objective: To perform a morphological evaluation concerning the extent of interproximal enamel reduction (IPR) with different manual instruments in different types of teeth and a qualitative analysis of enamel surface characteristics at the contact point before and after IPR. Material and Methods: 40 freshly extracted, caries-free, and intact human teeth were used for the study (20 bicuspids and 20 incisors) and performed IPR just on the mesial surface. The morphological variation of contact point was evaluated by superimposed the stl file, obtained thanks to an extraoral scanner, at T0 and T1 for each tooth. Two types of strip were used, Intensiv Manual Ortho Strips Coarse/Medium and Steelcarbo Horico Strips. Teeth were then cut lengthwise, removed the most apical root portion and the mesial and distal halves were gilded and observed at different magnifications. Results: The morphological variation following stripping mainly depends on the extent of the stripping, while the diameter, the type of strip and the shape of the tooth itself do not appear to be relevant. The 500X and 1500X magnifications allowed to appreciate better the characteristics of the surface of the stripped enamel and the differences with the intact enamel. All teeth treated, independently from the kind of strip used, shows deep marks and grooves in the direction of stripping. In both cases, the enamel appears significantly damaged at great magnifications . Conclusion: Stripping always and inevitably leads to a change in the shape of the contact point and is directly correlated to the amount of stripping performed. The use of polishing after the removal of enamel interproximal is necessary in all cases.